2016
DOI: 10.3389/fpls.2016.01288
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Understanding of Nanoparticle Uptake in Watermelon Plants

Abstract: The use of agrochemical-nutrient fertilizers has come under scrutiny in recent years due to concerns that they damage the ecosystem and endanger public health. Nanotechnology offers many possible interventions to mitigate these risks by use of nanofertilizers, nanopesticides, and nanosensors; and concurrently increases profitability, yields, and sustainability within the agricultural industry. Aerosol based foliar delivery of nanoparticles may help to enhance nanoparticle uptake and reduce environmental impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
140
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(145 citation statements)
references
References 37 publications
(37 reference statements)
4
140
0
1
Order By: Relevance
“…This indicates that the phloem tissue is the unique pathway for upward and downward translocation of nanoparticles in plant body and confirms the penetration of nanoparticles to plant leaves and accounts for the variable changes noticed in yield parameters and life span of nanofertilized wheat plants. This is in support with the work of W ang et al (2013) and Raliya et al (2016) who indicated that phloem is the main pathway for transport of nanoparticles (Fe, Zn, Mg, Ti, and Au) sprayed on leaves of water melon and transported through stomata to stem and roots through phloem.…”
Section: Discussionsupporting
confidence: 72%
“…This indicates that the phloem tissue is the unique pathway for upward and downward translocation of nanoparticles in plant body and confirms the penetration of nanoparticles to plant leaves and accounts for the variable changes noticed in yield parameters and life span of nanofertilized wheat plants. This is in support with the work of W ang et al (2013) and Raliya et al (2016) who indicated that phloem is the main pathway for transport of nanoparticles (Fe, Zn, Mg, Ti, and Au) sprayed on leaves of water melon and transported through stomata to stem and roots through phloem.…”
Section: Discussionsupporting
confidence: 72%
“…6), which might activate the metabolic events that are vital for the seed germination and seedling growth. The pathway of nanoparticle transport through the xylem and phloem in corn, tomato, and watermelon has been verified previously [45][46][47] . Internalized nanoparticles are transported through the vascular system of the phloem and could induce gene expression 48 resulting in the enhanced physiological parameters and ultimately productivity.…”
Section: Scientific Reports |mentioning
confidence: 68%
“…Size seems to be one of the main restrictions for penetration into plant tissues, and there are some reports about the maximum dimensions that plants allow for nanoparticles to move and accumulate inside the cells, usually with 40-50 nm as a size exclusion limit (González-Melendi et al, 2008;Corredor et al, 2009;Sabo-Attwood et al, 2012;Taylor et al, 2014). Additionally, the type of nanoparticle and its chemical composition is another factor influencing the uptake (Ma et al, 2010;Rico et al, 2011), whereas morphology has also been demonstrated as determinant in some cases (Raliya et al, 2016). Functionalization and coating of the nanomaterial surface can greatly change and alter the properties for its absorption and accumulation by the plant (Judy et al, 2012).…”
Section: Plant Absorption and Uptake Of Nanoparticlesmentioning
confidence: 99%
“…Indeed, some nanomaterials can be stopped and accumulated at the Casparian strip (Larue et al, 2012;Sun et al, 2014;Lv et al, 2015). Another important symplastic transport is possible too, using the sieve tube elements in the phloem, and allowing distribution toward non-photosynthetic tissues and organs Raliya et al, 2016). In the case of foliar applications, nanomaterials must cross the barrier the cuticle presents, following the lipophilic or the hydrophilic pathway (Schönherr, 2002).…”
Section: Movement Of Nanoparticles Inside Plantsmentioning
confidence: 99%